Telaah pemikiran Abdul Wahab Chasbullah tentang fiqih kebangsaan: Kemerdekaan dan persatuan Indonesia - Nurulloh, Muhammad Hasib; Mahendratama, Panji Dimas; Yulianto, Yulianto (Maliki Interdisciplinary Journal, 2024)
Abdul Wahab Chasbullah is known as a diligent cleric whose struggle has played a major role in advancing Indonesian independence and unity. Fiqh considerations were a very significant element for him in establishing guidelines for the struggle of the Indonesian nation. Abdul Wahab Chasbullah’s understanding of national jurisprudence is reflected in the spirit of love for the homeland as an expression of belief recognizing the existence of Indonesian culture as a characteristic of national identity, considering politics as a tool to achieve goals, and seeing religion as a source of inspiration. And wholeheartedly accept the ideology of Pancasila as a pillar of the unification of the Indonesian nation. Maintaining independence is a very essential step to achieve goals in aspects of religion and national and state life, in Kiai Wahab’s view. Apart from that, Kiai Wahab believes that unity is the main key in the struggle to fight colonialism, and without unity independence cannot be achieved. Kiai Wahab identified four different types of unity, namely social solidarity based on NU ties (ukhuwah Nahdiyah), Islamic ties (ukhuwah islamiyah), national ties (ukhuwah wathaniyah), and humanitarian ties (ukhuwah insaniyah). Keywords: Abdul Wahab Chasbullah, National Fiqh, Independence, Indonesian Unity and Implementation of National Fiqh